Intellectual cultivation: Quranic perspective in light of Surat Al-Kahf - Hamdeh, Basel Munir; Elatrash, Radwan Jamal Yousef (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia., 2019)
This article attempts to explore the Quranic instructions that contribute to intellectual growth. Intellectual cultivation is the process of developing our mental capacity in order to make sense of things and comprehend them on a deeper level. The inductive method and the analytical method will be used to study and categorize the Quranic guidelines found in Surat al-Kahf that if implemented will empower a person’s critical thinking. The study shows that the believer is distinguished with a clear awareness, thought, and vision of the reality of life and its occurrences. The research will also discuss the role of reflection and other spiritual practices such as Dhikr (remembering Allah), khalwa (meditating in solitude), shukr (gratitude) in the enhancement of our intellectuality and spiritual awareness.